Perfusion cultures require optimum respiratory ATP supply to maximize cell‐specific and volumetric productivities. Issue 5 (29th January 2019) - Becker, Max; Junghans, Lisa; Teleki, Attila; Bechmann, Jan; Takors, Ralf
Abstract: Perfusion processes are an emerging alternative to common fed‐batch processes in the growing biopharmaceutical industry. However, the challenge of maintaining high cell‐specific productivities remains. In this study, glucose limitation was applied to two perfusion steady states and compared with a third steady state without any detectable limitation. The metabolic phenotype was enhanced under glucose limitation with a decrease of 30% in glucose uptake and 75% in lactate formation. Cell‐specific productivities were substantially improved by 50%. Remarkably, the productivities showed a strong correlation to respiratory adenosine triphosphate (ATP) supply. As less reduced nicotinamide adenine dinucleotide (NADH) remained in the cytosol, the ATP generation from oxidative phosphorylation was increased by almost 30%. Consequently, the efficiency of carbon metabolism and the resulting respiratory ATP supply was crucial for maintaining the highly productive cellular state. This study highlights that glucose limitation can be used for process intensification in perfusion cultures as ATP generation via respiration is significantly increased, leading to elevated productivities. Abstract : In this study, glucose limitation was applied to two perfusion steady states and compared with a third steady state without any detectable limitation. Differences in metabolic efficiency could be tracked, with a strong effect of glucose limitation on carbon metabolism and ATP supply resulting in elevated productivities. Increased product formation rates were induced by significantly elevated ATP supply from oxidative phosphorylation.